Queue System Implementation at PT. Mulia Persada Indonesia Call Center Services - Haryani Haryani; Choirunisa Iqbar Qurotaaini; Cucu Ika Agustyaningrum; Artika Surniandari; Dedi Saputra (Paradigma - Jurnal Komputer dan Informatika, 2023)
In this modern era, call centers have become an important element in providing efficient and responsive customer service. One of the main challenges faced by call centers is how to efficiently manage customer call queues. This study aims to implement a queuing system at PT Mulia Persada Indonesia's call center service by utilizing a computer network, with the aim of increasing the efficiency and effectiveness of customer service. This research also includes an analysis of network security using a Virtual Private Network (VPN) and point-to-Point Tunneling Protocol (PPTP) as a security method for call center network connections. The results of the study show that the use of PPTP in PT Mulia Persada Indonesia's network security provides significant benefits. Call center employees can connect to the corporate network through a secure connection, even from an external location such as home. This access allows them to access the queuing system and perform call center tasks effectively without having to be in a physical office. Meanwhile, the implementation of a queue system at PT Mulia Persada Indonesia's call center service has had a positive impact, namely increasing customer satisfaction. With an effective queuing system, customer waiting time can be minimized and calls can be handled quickly.